2005
DOI: 10.1152/ajpheart.01009.2004
|View full text |Cite
|
Sign up to set email alerts
|

In vivo adenosine receptor preconditioning reduces myocardial infarct size via subcellular ERK signaling

Abstract: . In vivo adenosine receptor preconditioning reduces myocardial infarct size via subcellular ERK signaling. Am J Physiol Heart Circ Physiol 288: H2253-H2259, 2005. First published January 14, 2005 doi:10.1152/ajpheart.01009.2004.-The protective effects of adenosine receptor acute preconditioning (PC) are well known; however, the signaling mechanism mediating this effect has not been determined in in vivo models. The purpose of this study was to determine the role of the extracellular signal-regulated kinase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
52
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 35 publications
3
52
0
Order By: Relevance
“…Stimulation of both adenosine A 1 and A 2a receptors is associated with the activation of multiple protein kinases that have been implicated in cardioprotection (11,29,36). In a previous study (29), we reported that ZM-241385 appeared to blunt AMP579-mediated increases in the phosphorylation of the myocardial mitogenactivated protein kinase, extracellular signal-regulated kinase, before ischemia.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Stimulation of both adenosine A 1 and A 2a receptors is associated with the activation of multiple protein kinases that have been implicated in cardioprotection (11,29,36). In a previous study (29), we reported that ZM-241385 appeared to blunt AMP579-mediated increases in the phosphorylation of the myocardial mitogenactivated protein kinase, extracellular signal-regulated kinase, before ischemia.…”
Section: Discussionmentioning
confidence: 81%
“…Stimulation of both adenosine A 1 and A 2a receptors is associated with the activation of multiple protein kinases that have been implicated in cardioprotection (11,29,36). In a previous study (29), we reported that ZM-241385 appeared to blunt AMP579-mediated increases in the phosphorylation of the myocardial mitogenactivated protein kinase, extracellular signal-regulated kinase, before ischemia. Our observations that the A 2a agonist alone did not induce cardioprotection, but the antagonist ZM-241385 blocked protection induced by A 1 activation, suggest that occupation of the A 2a and/or A 2b receptor, either by the A 1 agonist or by increases in endogenous adenosine during ischemia or reperfusion, is necessary for adenosine A 1 receptormediated cardioprotection.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Coupling to K + channels in supraventricular tissue is responsible for the bradycardiac effect of adenosine on heart function 12 . In the heart, A 1 AR and A 2A AR agonistinduced preconditioning has been suggested to occur via modulation of p44/42 extracellular signal-regulated protein kinase (ERK) signalling 13 .…”
Section: Ar Signalling Pathways and Regulationmentioning
confidence: 99%